Generation of Genome Integration-free Induced Pluripotent Stem Cells from Fibroblasts of C57BL/6 Mice without c-Myc Transduction - Jincho, Yuko (American Society for Biochemistry and Molecular Biology, 2010)
Although the induction of genome integration-free induced pluripotent stem cells (iPSCs) has been reported, c-Myc was still required for the efficient generation of these cells. Herein, we report mouse strain-dependent differences in the c-Myc dependence for iPSC generation and the successful generation of genome integration-free iPSCs without c-Myc transduction using C57BL/6 mouse embryonic fibroblasts. We performed 49 independent experiments and obtained a total of 24 iPSC clones, including 18 genome integration-free iPSC clones. These iPSCs were indistinguishable from embryonic stem cells and from iPSCs generated using other methods. Furthermore, the generation of three-factor iPSCs free of virus vectors revealed the contribution of c-Myc to the genomic integration of external genes. C57BL/6 is an inbred mouse strain with substantial advantages for use in genetic and molecular biological studies due to its use in the whole mouse genome sequencing project. Thus, the present series of C57BL/6 iPSCs generated by various procedures will serve as a valuable resource for future genetic studies of iPSC generation.